The implication of Green HRM and how it affects organizational goals in the HR department of Bangla Cat Company Ltd - Gomes, Reya Florence (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.